Socialization of the 'NAMISIKU' Application for the Prevention of Postpartum Depression in Mothers - Syastriani Isna Putri Syarif; Dwi Yuliani Adnan (Yayasan Ahmad Mansyur Nasirah, 2026)
Postpartum depression is a condition that must be given serious attention because it affects not only the mother, but also the child, and harmony within the family. Therefore, healthcare providers, families, and the community need to have anunderstanding of how to detect and manage this condition effectively. This community service aims to improve mental health literacy and digital skills of postpartum mothers through the use of the NAMISIKU application. The activity was carried out using a participatory approach with the following stages : a) socialization and education, b) training and application usage, c) monitoring and evaluation. The results show that there was an increase in mental health literacy among postpartum mothers, as indicated by a 70% improvement in knowledge related to postpartum depression symptoms and the importance of social support, based on pre-test and post-test results. In addition, training on the use of the NAMISIKU application successfully enhanced participants' skills in accessing and utilizing digital features, with most postpartum mothers able to operate the application independently. The participants also responded positively, expressing satisfaction with its content, design, and usefulness in recognizing emotional symptoms and finding appropriate information. The conclusion is that the program showed a 70% increase in understanding, a 90% improvement in application usage skills, and an 80% level of participant satisfaction, indicating that the NAMISIKU application has strong potential as a screening and educational tool for the prevention of postpartum depression.